2016
DOI: 10.1111/1346-8138.13695
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of high mobility group box‐1 in imiquimod‐induced psoriasis‐like mice model

Abstract: In the previous work, we have indicated that HMGB1, a pro-inflammatory cytokine, is closely associated with the pathogenesis of psoriasis. To further clarify the role of HMGB1 in the pathogenesis of psoriasis, we investigated the direct function of HMGB1 application and HMGB1 blockade in imiquimod (IMQ)-induced psoriatic mouse model in this study. Mice were treated with imiquimod (IMQ) to induce psoriasis-like inflammation, and consecutively injected with recombinant HMGB1 or phosphate-buffered saline (PBS) i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…Despite GL's anti-viral and anti-inflammatory effects, these two inhibitors displayed comparable in vitro and in vivo suppressive efficiencies in angiogenic activities. It was once again demonstrated that GL acts as a direct inhibitor of HMGB1 [48] and, consistent with a previous report [49], GL exerts similar effectiveness as anti-HMGB1 mAb. To the best of our knowledge, this report provides the first evidence that HMGB1 encountered within the TME closely interacts with B cells for the secretion of proangiogenic factors that promote angiogenesis.…”
Section: Discussionsupporting
confidence: 90%
“…Despite GL's anti-viral and anti-inflammatory effects, these two inhibitors displayed comparable in vitro and in vivo suppressive efficiencies in angiogenic activities. It was once again demonstrated that GL acts as a direct inhibitor of HMGB1 [48] and, consistent with a previous report [49], GL exerts similar effectiveness as anti-HMGB1 mAb. To the best of our knowledge, this report provides the first evidence that HMGB1 encountered within the TME closely interacts with B cells for the secretion of proangiogenic factors that promote angiogenesis.…”
Section: Discussionsupporting
confidence: 90%
“…It has been reported that glycyrrhizin can effectively inhibit the cytoplasmic transduction of HMGB1. Our previous studies also found that glycyrrhizin can target the inhibition of cytoplasmic transduction in HMGB1 and thus inhibit the expression of inflammatory cytokines, and it has been proven that glycyrrhizin is a direct inhibitor of HMGB1 ( 13 ). This study used glycyrrhizin to effectively treat vasculitis mice and reduce inflammation.…”
Section: Discussionmentioning
confidence: 90%
“…The high mobility group box 1 protein (HMGB1) is universal in all the cells of higher eukaryotes, is secreted by inflammatory cells (such as: activated monocytes, macrophages, mature dendritic cells, and natural killer cells), and may act as a potent mediator of inflammation ( 17 20 ). Our previous work found that the expression of HMGB1 was elevated in a variety of vasculitis diseases, and it was decreased in patients with HSP after treatment ( 13 ). HMGB1 may play an important role in the pathogenic mechanism of vasculitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the total mass of IMQ distributed daily to each mouse is 3.125 mg. This dose has been empirically determined [ 4 ] and already demonstrated to cause reproducible and optimal skin inflammation in this model in various publications [ 7 , 27 , 31 , 32 , 33 ]. The control group was treated similarly with Lanette cream containing cetyl stearyl alcohol (BASF, Ludwigshafen, Germany).…”
Section: Methodsmentioning
confidence: 99%